CERDAS FINANSIAL SEJAK DINI: EDUKASI DASAR LITERASI KEUANGAN DAN RISIKO PINJAMAN ONLINE DI SD NEGERI 1 SINGAPADU TENGAH - Ni Wayan Suastini; Ni Nyoman Cindy Hapriliani; I Gusti Ayu Sri Laksmi Wulandari (LOKATARA SARASWATI, 2026)
A community service activity themed "Early Financial Intelligence: Basic Financial Literacy Education and Online Loan Risks" was conducted at SD Negeri 1 Singapadu Tengah, Gianyar, Bali. This program aimed to enhance 5th- and 6th-grade students' understanding of basic financial literacy and the risks associated with online loans. Based on initial observations, it was found that the students had a minimal understanding of financial management, the distinction between needs and wants, and the risks of using Fintech Loans. The implementation methods included observation, interviews, preparation and design, execution, and closing. Education was delivered through an engaging approach, including interactive discussions and rewards to increase student participation. The results of the activity showed an improvement in students' understanding of basic financial literacy concepts, including how to manage money wisely and how to recognize the risks of fintech loans. High enthusiasm from the students, as well as active support from teachers and the school principal, were supporting factors for the success of this program. In conclusion, this program successfully increased students' financial literacy, making them better prepared to face future financial challenges. It is recommended that financial literacy be integrated into the formal education curriculum to cultivate a younger generation that is financially literate and capable of managing their finances wisely.